ANALISIS KINERJA RANTAI PASOK AGROINDUSTRI KOPI ARABIKA DI KABUPATEN ACEH TENGAH PROVINSI ACEH - Elfiana; Desparita, Naya; Husna, Naziratil (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2023)
Aceh Province is a leading national coffee producing province, one of the coffee producing centers in Aceh is Central Aceh Regency with the area planted with coffee plants in 2022 reaching 49,997/ha and coffee production reaching 36,060 tons/year. Coffee has economic value from both the farmer level and the final consumer. What often happens is that the value obtained by farmers is not equal to that obtained by other marketing institutions in the supply chain and coffee value chain, so adding value to coffee requires product development and maximum utilization of resources. by generating profits in all lines of institutions involved. The role of the Arabica coffee agroindustry is very helpful in developing coffee into finished products or processed coffee-based products, so that all systems in the coffee supply chain benefit. Apart from that, the role of the Arabica coffee agroindustry will have an impact on the value chain of Arabica coffee produced in Central Aceh Regency. The research method used is descriptive and quantitative analysis using the AHP Matrix. The results obtained show that the performance of the Arabica coffee agroindustry supply chain in 13 agroindustries in Central Aceh is at a below average level, extra improvement is needed to be able to obtain a good or excellent level.